The 260-W coherent beam combining of two compact fibre amplifier chains - 王小林 马阎星 周朴 何兵 薛宇豪 刘驰 李震 肖虎 许晓军 周军 刘泽金 赵伊君 (Chinese physics B, 2011)
Coherent beam combining of two fibre amplifier chains with a total power of 260 W in a compact system using the stochastic parallel gradient descent （SPGD） algorithm is demonstrated. A 150 MHz linewidth fibre laser is built and introduced for high-power amplification to mitigate stimulated Brillouin scattering （SBS）. Compact high-power amplifier chains are built with low power all-fibre system and high-power bulk free-optics fibre amplifiers. When the total power is about 260 W, active phase-locking of two high-power amplifiers is demonstrated using the SPGD algorithm. In closed-loop, the power in the main lobe increases 1.68 times, the visibility is increased from 0 to 0.62, and the phase residual error is less than λ/10.